Enhancing HTML5 Games Accessibility : An Exploration of Assistive Technology for People with Visual Impairments - Chen, Xuexian (My University, 2024)
Digital games have offered enjoyment to countless people, however, people with disabilities are often excluded from these experiences. Visually impaired individuals, in particular, encounter challenges in gaming as the majority of digital games heavily rely on graphics and visual content. While there are accessible games, such as audio games, tailored for them, there remains a lack of an assistive tool that can support a wide range of digital games. To fill this gap, this thesis aims to explore the feasibility of a universal assistive technology to support multiple HTML5 games. HTML5 games are a subset of web games that can be played via web browsers without the need for installation. An assistive technology prototype in the form of a Chrome extension was developed in this thesis, with a requirements design drawing insights from existing accessibility guidelines and related accessible games. The prototype covers common accessibility features such as font, cursor customization and magnifier, along with advanced features including narration, highlight and sonification. Exploratory testing and task-based usability testing were conducted to evaluate the prototype. Testing results indicate that most features of the prototype can effectively enhance game accessibility, yet some require further optimization. Despite limitations, this work sets a solid foundation for further research and development in this area.
Keywords: HTML5 game, Assistive technology, Accessibility, Sonification, Chrome extension, Audio game, Accessibility guideline